Usaha Mikro, Kecil, dan Menengah (UMKM) konveksi di Desa Turen: Sejarah, tantangan, dan strategi perekrutan karyawan - Abdillah, Mochammad Nizar (Maliki Interdisciplinary Journal, 2024)
Turen Village is one of the villages targeted by our group, namely the 183 Digantara group. Then the village also became one of the objectives of the community service program at UIN Maulana Malik Ibrahim Malang. Turen Village is located in Malang Regency, Turen District. Micro, Small and Medium Enterprises (MSMEs) have an important role in regional economic development, regional governments should pay attention to the growth and development of business fields. Regional governments must make a real contribution to MSMEs in maintaining existing products at a time when many imported products are entering the domestic market. The main problem faced by MSMEs towards digitalization is that human resources are still low and access to technology is not yet widespread, so to face these challenges there must be assistance and education for business people who want change. Efforts to make MSMEs face the digital era must include an empowerment movement.